Prenatal ultrasonographic diagnosis of urethral atresia - Thapa, N B; Dwa, Y; Gurung, S; Baral, R (Journal of Institute of Medicine Nepal, 2010)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Urethral atresia is one of the rare congenital anomaly of urogenital tract. In this case report, uretheral atresia diagnosed antenatally by ultrasonography (USG) at 24-25 weeks of gestation is presented. USG findings were confirmed by postmortem examination of the fetus. Key words: Lower urinary tract obstruction, posterior urethral valves, ultrasonography, urethral atresia, DOI: 10.3126/joim.v31i3.3001 Journal of Institute of Medicine, December, 2009; 31(3) 61-62